Study of information search strategies used in the CAPES Portal of E-Journals - Ribeiro, Nádia Ameno; Cendón, Beatriz Valadares (Qualitative and Quantitative Methods in Libraries; Vol 6 No 1 (2017): March 2017 Issue, 2019)
The present research evaluated the search strategies used by faculty in the CAPES Portal of E-Journals. The faculty selected for carrying out this research were distributed throughout 17 Brazilian federal universities. Data was collected by means of a web-survey which used a mainly quantitative methodology, with some qualitative data. Users received four questionnaires via email. The present study selected responses for one question (number 14) of the second questionnaire which were quantitatively analyzed . The analysis revealed that 79,2% (4100) of the respondents), when searching for a subject, initially search a reference database in the Portal to identify articles or journals and, only after that, access the full text journal databases to obtain the full text. The research also analyzed qualitative data in the open field of question 14 where users cited other search strategies used in the Portal. Categories that emerged from the analysis of the content went through successive refinements. The analysis subdivided 507 comments into eight initial categories, which were regrouped into three main categories according to their content similarity: (1) Users search for bibliographic references and full text using the CAPES Portal of E-Journals interface; (2) Users search for bibliographic references and full-text directly in the databases websites without using the CAPES Portal of E-Journals interface; (3) Users search for bibliographic references in other electronic resources, and then use CAPES Portal of E-Journals interface to obtain the full text. It was found that category (3) stood out with the highest percentage (49,5%) of the valid comments, while category (1) obtained 33% of the comments, followed by category (2), which contained 17,5% of the comments. The results obtained in qualitative analysis, show that a part of the users do not use the CAPES Portal search capabilities to find the article, but only as a mean to obtain free access to the full text of the publications. The article presents recommendations of further research and actions to improve use of the Portal and other similar information resources.